SYNTHESIS, CHARACTERIZATION AND INSILICO TOXICITY PREDICTION, ANTI-MICROBIAL STUDY OF ORTHO-AMINO SUBSTITUTED BENZAMIDE DERIVATIVES: Pharmaceutical Science-Medicinal Chemistry - SK. AMMAJI; G.PAVAN KUMAR; K.LIKHITH; K. MADHUSREE; K. POOJA; P.VENKATESH (International Journal of Life Science and Pharma Research, 2019)
Benzamides are most widely used in medicinal chemistry and play a key role in biological action for treatment of various disorders such as anti-microbial, anti-malarial, anti-cancer, anti HIV, anti-viral, anti ameobic, anti-psychotic. The benzamide was used as an intermediate for synthesis of various medicinal compounds, in the present work; synthesization was carried out by using isatoic anhydride treated with various substituted anilines under acidic condition to form different substituted ortho-amino benzamide derivatives. Evaluation of the synthesized compounds were done by using the Insilico toxicity prediction methods with the aid of online software’s like OSIRIS, OCHEM, Molinspiration. These three softwares gave the drug score value of 3a, 3c, 3f, 3d and they are nearer to standard drug score value of 0.8. Toxicity prediction inferred that except 3e, other derivatives were safe to inhibit enzyme cytochrome P450 a subunit of CYP 1A2. The enzyme located in endoplasmic reticulum metabolizes the polyunsaturated fatty acids, steroidal hormones, vitamins, and also catalyzes hydroxylation reaction like hydroxyl estrogen from estrogen, 17-beta estradiols and has a major role in synthesis of all Trans retinol biosynthesis in liver. Invitro evaluation of Anti-microbial activity done by disc diffusion method, confirmed the compounds3eand3f had significant activity against Pseudomonas aeruginosa and the compounds3aand3dshowed significant activity against Bacillus subtilis, whereas the compounds 3c showed good activity against the organism Bacillus pumilus. Compound 3a showed moderate antifungal activity against Candida albicans. Thus in future benzamides can be considered as an effective intermediate for synthesis of different substituted quinoxaline derivatives.